An update of distribution, habitats and conservation status of the Indian pangolin (Manis crassicaudata) in Sri Lanka - Perera, P.; Karawita, H. (Elsevier, 2019)
The Indian pangolin (Manis crassicaudata) is the only pangolin species present in Sri Lanka. Growing concerns over international trading and trafficking of pangolins and the recent listing of all eight extant pangolin species in Appendix I of CITES have generated considerable interest in M. crassicaudata among conservationists in Sri Lanka. However, only limited research has investigated the distribution, abundance, and threats to Indian pangolins and robust estimates of distribution, population size, and threats require intense research based on long-term data. This study presents an update on the distribution, knowledge of habitats and conservation status of the Indian pangolin in Sri Lanka based on an extensive data set collected from primary and secondary data sources. Our findings confirmed the occurrence of Indian pangolin in habitats up to 1850m above mean sea level with a higher concentration of Indian pangolin populations occurring in the North-west, North-central, South-west lowlands and South-eastern parts of the island. The species was mostly recorded from tropical shrubland, tropical dry forest, tropical moist lowland forest, tropical dry grassland and tropical heavily degraded former forest habitats. The findings of the study revealed that wildlife crimes related to the Indian pangolins are rising. Hunting for subsistence, live capture to sell as meat, hunting for scales, and traps intended for other agricultural pests are the main threats to M. crassicaudata in Sri Lanka. Recent confiscations of pangolin scales by law enforcement authorities and growing incidents of poaching pangolins for illegal trade hint at the existence of local niche markets for pangolin meat and scales with a possible international trading pathway of M. crassicaudata scales from Sri Lanka to South India. The data presented here provide important information for global and national conservation status assessment of M. crassicaudata, and an impetus for conservation planning for the species in Sri Lanka.
Keywords: Illegal wildlife trade Conservation Wildlife crimes Poaching Distribution